APLIKASI PRODUCT BUNDLING UNTUK MENDUKUNG PENERAPAN ASSOCIATION RULE MINING MENGGUNAKAN FP-GROWTH - Iin Ernawati; Nurhafifah Matondang (Jurnal Teknologi Informasi dan Pendidikan, 2021)
Online media has been proven to gave good impact especially in the business field, for opening and widen access to people and society, and so giving more opportunity to any business broader and easy access through electronic commerce (e-commerce). This is the basic idea for the need to improve business reach for a decorative plants store in Tangerang Area. The association transaction pattern as the outcome of data mining process by implementing the Fp-Growth Algorithm that is injected to a mobile application with the purpose to get the buyer’s shopping pattern, which is also packed as the products bundling promotion media and finally open the opportunity to broaden reach for business and information.